2013
DOI: 10.2147/hiv.s50726
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among people living with acquired immune deficiency syndrome receiving anti-retroviral therapy: a study from Nepal

Abstract: PurposeThe present study was undertaken to determine the impact of acquired immune deficiency syndrome (AIDS) on the quality of life of affected individuals in Nepal.Patients and methodsA cross sectional study was done among 70 individuals attending the Anti-Retroviral Therapy clinic of the University Hospital in Nepal. Quality of life (QOL) was evaluated using World Health Organization Quality of life questionnaire (WHO QOL-BREF) instrument. Statistical analysis was done using SPSS Version 17.0.ResultsThe med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
21
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 23 publications
(34 reference statements)
9
21
2
Order By: Relevance
“…This study demonstrated the importance of social demographic variables for quality of life for people dealing with HIV/AIDS. The largest portion of respondents affected were between 31 and 40 years of age and this finding is congruent with the report of Imam et al [11] and Giri et al [12].…”
Section: Discussionsupporting
confidence: 91%
“…This study demonstrated the importance of social demographic variables for quality of life for people dealing with HIV/AIDS. The largest portion of respondents affected were between 31 and 40 years of age and this finding is congruent with the report of Imam et al [11] and Giri et al [12].…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, the overall median percentage score of QoL was 71.29, which is lower than reported by Acharya [16] and Giri et al [17] (80.00) among Nepalese PLHIV, but higher than reported by Oliveira et al [18], (62.5) among Brazilian PLHIV. Other works in the literature in the African setting presented their QoL scores in means, therefore making direct comparison of scores with the current study not plausible [1, 6, 10].…”
Section: Discussioncontrasting
confidence: 85%
“…Present study reveals that most of the asymptomatic patients are in Pre ART group. There is a study 20 shown similar findings which has lower score among psychological domain. A low score in the psychological domain may be explained by the increased morbidity, negative feelings, and low self-esteem due to the perception of acquiring incurable disease 20 .…”
Section: Discussionsupporting
confidence: 55%
“…There is a study 20 shown similar findings which has lower score among psychological domain. A low score in the psychological domain may be explained by the increased morbidity, negative feelings, and low self-esteem due to the perception of acquiring incurable disease 20 . Psychological domain is affected by education which is low in present study, income, occupation, ART treatment (low mean score in ART group in present study), WHO clinical categories 23 .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation